THE ROLE OF SHARIA BANKS IN DEVELOPING THE ECONOMY IN INDONESIA - Masduqi Masduqi (UNISSULA, 2019)
Sharia banking whose management is based on sharia mechanisms emphasizes the vision of economic growth and economic development regarding profit sharing in accordance with the size of the contribution between the bank and the customer through a provit sharing system. So that through the Islamic banking system it is hoped that a positive synergy of economic growth and development will be formed. Where economic development places more emphasis on fundamentals for improved management and distribution between banks and customers through a proportional provit sharing system. So that it will create a system of cooperation that is mutually beneficial and at the same time stimulates economic growth and development. To be sure, in sharia banks is where profits and cost sharing are equally proportional to promoting justice. So indirectly the Islamic banks can offer product value or product proportion that is quite attractive to customers. A good customer relationship will be formed automatically with the customer so that each party can get the maximum benefits that have a direct impact on economic growth and development